the Patriarchal Picture in Oscar Wilde’s The Picture of Dorian Gray: Patriarchal Picture in Oscar Wilde’s The Picture of Dorian Gray - Fanani, Abu Fanani; Andini, Risky Eka Andini; Mufid, Nur Mufid; Thoriqussuud, Muhammad Thoriqussuud; Amiq, Amiq (Faculty of Letters, Universitas Dr. Soetomo, Surabaya, Indonesia, 2025)
Patriarchy refers to the domination of men over women in all kinds of field. Women have no rights to do what men can do. There are a lot of studies about patriarchy, most of which are about man’s power towards woman with the result of woman’s struggle to get equality with the man that is called feminism. This study challenges the previous studies above that study on patriarchy does not always get the responses of feminism. In Oscar Wilde’s the Picture of Dorian Gray, the researcher studies about patriarchal picture. How the characters Lord Henry Wotton and Dorian Gray reveal their patriarchal words towards women is discussed in this study. Using close reading as a method, this study shows the result that the two men, Lord Henry Wotton and Dorian Gray reveal words about women that are patriarchal: symbolizing women, oppressing women’s voices, and manipulating as well as abusing women’s emotion that the researcher suggests their words can put women in degradation as well as humiliation that feminist should fight for. Besides, the impacts on women, that is the loss of women’s dignity, are also the finding of the study.